2018
DOI: 10.3389/fmicb.2018.01692
|View full text |Cite
|
Sign up to set email alerts
|

Traits-Based Integration of Multi-Species Inoculants Facilitates Shifts of Indigenous Soil Bacterial Community

Abstract: Microbial co-inoculation is considered to be an innovative approach and had been applied worldwide. However, the underlying mechanisms of microbial co-inoculants constructions, especially the trait-based combination of distinctly different microbial species remains poorly understood. In this study, we constructed two microbial co-inoculants with the same three strains with emphasis on the microbial, soil and plant traits. Microbial co-inoculants 1 (M1) were constructed according to soil fertility, microbial ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 55 publications
(71 reference statements)
1
28
0
Order By: Relevance
“…In addition, PGPR inoculation in the present study obviously changed the structure of bacterial communities in the maize rhizosphere as detected using MiSeq high‐throughput sequencing technology (Figs 2 and 3; Table S6). Previous studies have reported that PGPR inoculation may regulate the composition of the host rhizobacterial communities (Zhang et al ., 2019b,c), and different inoculants have different effects on root‐associated bacterial communities, which may indirectly affect plant growth (Gadhave et al ., 2018; Wang et al ., 2018). In the current study, the abundance of certain bacterial populations in the maize rhizosphere was decreased or increased to various degrees after inoculation with the four PGPR strains (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, PGPR inoculation in the present study obviously changed the structure of bacterial communities in the maize rhizosphere as detected using MiSeq high‐throughput sequencing technology (Figs 2 and 3; Table S6). Previous studies have reported that PGPR inoculation may regulate the composition of the host rhizobacterial communities (Zhang et al ., 2019b,c), and different inoculants have different effects on root‐associated bacterial communities, which may indirectly affect plant growth (Gadhave et al ., 2018; Wang et al ., 2018). In the current study, the abundance of certain bacterial populations in the maize rhizosphere was decreased or increased to various degrees after inoculation with the four PGPR strains (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Wang et al . (2018) reported that inoculation with a mixture of Ensifer sp. NYM3, Acinetobacter sp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ke et al [39] reported that the inoculation of soil with Pseudomonas stutzeri A1501 significantly changed the indigenous soil bacterial community structure after 2 months of inoculation, and our findings are consistent with this report. Similarly, Wang et al [40] discussed the significant effect of bio-inoculants on soil microbial communities. In this study, the abundance of the Ellin 329 and Rhizobiales orders were higher in all samples.…”
Section: Discussionmentioning
confidence: 99%
“…In order to enhance the reliability and efficacy of microbial inoculants in agriculture and combining these PGPB by co-inoculation had been applied worldwide for more than a decade. As co-inoculation would mimic the natural situation more closely and allow the combination of various mechanisms without the need for genetic engineering [12].…”
Section: Introductionmentioning
confidence: 99%